2003
DOI: 10.1634/theoncologist.8-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Receptors in Breast Cancer: Potential for Therapeutic Intervention

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 119 publications
(112 reference statements)
0
73
0
2
Order By: Relevance
“…Alternatively, the neutralizing ability may be due to antibody 733 interfering with the interaction of heparanase with its substrate. Given the specificity of antibody reaction and the recent therapeutic use of antibodies in the clinic (Ludwig et al, 2003;Nahta et al, 2003), neutralizing anti-heparanase antibodies are extremely important reagents for basic heparanase research and, possibly, clinical applications. Raising monoclonal antibodies against the 14 amino acid sequence recognized by antibody 733 is hoped to yield an even better neutralizing ability and is currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the neutralizing ability may be due to antibody 733 interfering with the interaction of heparanase with its substrate. Given the specificity of antibody reaction and the recent therapeutic use of antibodies in the clinic (Ludwig et al, 2003;Nahta et al, 2003), neutralizing anti-heparanase antibodies are extremely important reagents for basic heparanase research and, possibly, clinical applications. Raising monoclonal antibodies against the 14 amino acid sequence recognized by antibody 733 is hoped to yield an even better neutralizing ability and is currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel tyrosine kinase inhibitors, such as the quinazolines, gefitinib, and erlotinib, function as competitive inhibitors at the tyrosine kinase ATP-binding site (32), while some are functional on RA synovial fibroblasts (33). Therapies directed against HER-2 and EGFR abound in breast, epithelial, ovarian, gut, and non-small-cell lung cancer (13,34,35). It has been reported that downstream signaling from phosphorylated tyrosine kinase domains of ErbB receptors uses different pathways for pro-versus antiangiogenic factors, a critical feature in modulation of the homeostatic balance of physiologic versus pathologic angiogenesis (36).…”
Section: Discussionmentioning
confidence: 99%
“…20), and Ras family proteins (21,22) are mutated, amplified, or hyperactivated in many human cancers. Furthermore, in several epithelial cell models, including the murine mammary epithelial cell line EpH4, metastatic potential requires the cooperation of TGF-b signaling with hyperactive ERK/MAPK signaling, caused by oncogenic RTKs (e.g., HER2), Ras, or Raf (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%